202k views
4 votes
Which of the following is the correct equation for this function?

Which of the following is the correct equation for this function?-example-1
User Varrunr
by
5.0k points

1 Answer

2 votes

we know that

The graph represent a vertical parabola

The equation of a vertical parabola open upward in vertex form is equal to

y=a(x-h)^2+k

where

a is the leading coefficient

(h,k) is the vertex

In this problem we have

the vertex is (-3,-2) -----> see the graph

substitute

y=a(x+3)-2

Find the value of a

we have that

For x=-2, the valuue of y=0

substitute

0=a(-2+3)^2-2

0=a-2

a=2

therefore

the equation is

y=2(x+3)-2

REwrite

y+2=2(x+3)^2

User Kenton Price
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.